2017
DOI: 10.1093/ajae/aax040
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Cost Sharing and Water Quality in the Chesapeake Bay: Estimating Indirect Effects of Environmental Payments

Abstract: This article analyzes the effect of agricultural cost sharing for cover crops on the acres of three conservation practices. A survey of farmers from Maryland is used to estimate the direct effect of cover crop cost sharing on the acres of cover crops, and the indirect effect of cover crop cost sharing on the acres of two other practices: conservation tillage and contour/strip cropping. A two‐stage simultaneous equation approach is used to correct for voluntary self‐selection into cost‐sharing programs, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
1
31
2
Order By: Relevance
“…Incentives to cover some of the supplementary costs and additionally incurred risks are required to encourage adoption. A study by Fleming (2017) found that most producers adopting CCs receive cost share. He found an increase in CCs acreage due to cost sharing as well as additional conservation tillage acreage, thereby suggesting some practice complementarity.…”
Section: Complementarity In the Adoption Of Conservation Practicesmentioning
confidence: 99%
“…Incentives to cover some of the supplementary costs and additionally incurred risks are required to encourage adoption. A study by Fleming (2017) found that most producers adopting CCs receive cost share. He found an increase in CCs acreage due to cost sharing as well as additional conservation tillage acreage, thereby suggesting some practice complementarity.…”
Section: Complementarity In the Adoption Of Conservation Practicesmentioning
confidence: 99%
“…Regarding cover crops specifically, Chabé-Ferret and Subervie (2013) estimated that PES programs in France increase cover-crop acreage by 27 ac (11 ha) per farm. In the USA, studies in Maryland (Lichtenberg and Smith-Ramirez, 2011;Fleming, 2017;Fleming et al, 2018) and Ohio (Mezzatesta et al, 2013) found that crop farmers' enrollment in cost-share programs increased the share of acres under cover crops from 8 to 28%. Lastly, results from ongoing work by Gonzalez-Ramírez and Arbuckle (2016) indicate that that cost-share payments increase acreage share of cover crops by 18 percentage points among Iowa farmers, and Lee et al (2018) found that Iowa farmers who received cost-share or technical assistance were more than twice as likely to plant cover crops than those who did not.…”
mentioning
confidence: 99%
“…If the cost share rates for rotational grazing and water tanks were increased by 14.49% and 12.56% to their market values (100% cost share), then the corresponding change in acres in rotational grazing are 17.58%. For water tanks and rotational grazing, the incentive for their adoption appears to "crowd in" private investment in the form of additional acres in rotational grazing or additional water tanks (Fleming, 2017).…”
Section: Response To Incentives and Pasture Bmp Adoptionmentioning
confidence: 99%
“…A 1% increase in the incentive offered to adopt pasture improving practices corresponds with a −0.11% decrease in areas respondents are willing to manage with a rotational grazing system, thereby "crowding out" private investment (Fleming, 2017). The incentive for water tanks crowds out willingness to improve pasture as a 1% increase in the incentive offered to adopt a water tank is associated with a 0.54% decrease in the number of pasture acres respondents are willing to rehabilitate (Table 5).…”
Section: Response To Incentives and Pasture Bmp Adoptionmentioning
confidence: 99%